"Intelligent Construction, Digital Modeling of the Future" Internet + BIM Service EPC Project——Take the Exhibition Center of National Cybersecurity Center for Education and Innovation Project as an Example. Issue 2 (April 2021) - Jiang, Ming; Cheng, Yang; Lei, Ting; Liu, Zhuojun
Abstract: This paper discusses the application of Internet and BIM technology to serve the construction mode of "PPP +EPC+ Fund" and management mode of "Executive Architect". Taking the Exhibition Center of National Cybersecurity Center for Education and Innovation project as an example, relying on the CITIC Intelligent Construction Platform, BIM and digital technology such as cloud computing, big data, IOT, mobile Internet, chainblock etc., are used in the entire life cycle of the project, including design, procurement, construction and facility management. The data sharing and information management of the whole life cycle of the project are realized, which strongly supports the scientific construction and operation of the project.